PELATIHAN TEKNOLOGI PRODUKSI DAN PENINGKATAN MUTU KERUPUK BAWANG SEBAGAI STRATEGI PENINGKATAN PENDAPATAN USAHA MIKRO DI KECAMATAN BERINGIN, KABUPATEN DELI SERDANG - Suhairiani Suhairiani; Nur Basuki; Enny Keristiana Sinaga; Muhammad Reza; Muhammad Rifqi (Jurnal Abdi Insani, 2026)
The Community Service Program entitled “Improving Product Quality and Production Technology Training for Onion Crackers to Increase the Income of Micro, Small, and Medium Enterprises (MSMEs) in Beringin District, Deli Serdang Regency” was implemented to address issues related to low product quality and inefficient production processes among partner MSMEs. Field observations identified several problems, including manual production methods, inconsistent product quality, and limited packaging and marketing strategies. The implemented solutions included training in the use of simple production technologies such as dough mixer machines, automatic cutters, and controlled-temperature frying. In addition, participants received training in modern packaging and digital marketing through social media platforms. The program outcomes indicated increased production efficiency, more consistent product quality, and wider market reach. The partners showed strong enthusiasm in applying the introduced technologies, and the program successfully met its intended objectives.